Does the lack of financial stability impair the transmission of monetary policy? - Viral V. Acharya; Björn Imbierowicz; Sascha Steffen; Daniel Teichmann (Deutsche Bundesbank, 2019)
We investigate the transmission of central bank liquidity to bank deposits and loan spreads in Europe over the period from January 2006 to June 2010. We find evidence consistent with an impaired transmission channel due to bank risk. Central bank liquidity does not translate into lower loan spreads for high-risk banks for maturities beyond one year, even as it lowers deposit spreads for both high-risk and low-risk banks. This adversely affects the balance sheets of highrisk bank borrowers, leading to lower payouts, capital expenditures and employment. Overall, our results suggest that banks' capital constraints at the time of an easing of monetary policy pose a challenge to the effectiveness of the bank-lending channel and the central bank's lender-of- last-resort function.
Keywords: E43; E58; G01; G21; 330; Central bank liquidity; Monetary policy transmission; Corporate deposits; Financial crisis; Lender of last resort; Loans; Real effects